On the stability of a plane gyroscopic pendulum - Golinko, S. I. (Reports of the National Academy of Sciences of Ukraine, 2015)
The stability of a plane gyroscopic pendulum is considered. The system of differential equations of perturbed motion with impulsive action, using the special changes of variables, is reduced to a linear system of ordinary differential equations with constant coefficients. The conditions of existence of the parametric resonance of plane gyroscopic pendulum’s oscillations are obtained.